Intrauterine thoracentesis of congenital chylothorax: report of a case - Albinagorta Olórtegui, Roberto (2015)
Congenital chylotorax is a rare anomaly associated with high perinatal mortality when accompanied by hydrops fetalis. Thoracentesis and pleuroamniotic shunting have proven to be alternative successful options for antenatal treatment, but there is still controversy on which is first choice. In Peru there are no reports of similar cases treated in utero. We report a case of a 37½ weeks pregnancy affected with massive lateonset congenital chylotorax successfully treated by intrauterine thoracentesis. Adequate lung expansion was achieved, allowing the birth of a baby who did not present respiratory failure and did not require subsequent ventilatory support. This paper shows intrauterine thoracentesis is a viable treatment option for similar cases in Peru.